CTNI-20. RESULTS OF A PHASE 1/2 CLINICAL TRIAL OF BLOOD-BRAIN BARRIER (BBB) OPENING WITH THE SONOCLOUD-9 IMPLANTABLE ULTRASOUND DEVICE IN RECURRENT GLIOBLASTOMA PATIENTS RECEIVING IV CARBOPLATIN. (14th November 2022) - Carpentier, Alexandre; Sonabend, Adam M; Stupp, Roger; Chinot, Olivier; Dufour, Henry; Ducray, François; Menei, Philippe; de Groot, John; Weinberg, Jeffrey; Desseaux, Carole; Canney, Michael; Idbaih, Ahmed
Abstract: Low intensity pulsed ultrasound in combination with microbubbles can be used to temporarily disrupt the blood-brain barrier (BBB). A phase 1/2 clinical study (NCT03744026) was initiated to demonstrate the safety and efficacy of BBB disruption using an implantable ultrasound system (SonoCloud-9) in patients with recurrent glioblastoma receiving carboplatin chemotherapy. The SonoCloud-9 device, which contains nine, 1-MHz, 10-mm diameter ultrasound emitters (Carthera, Paris, France) was placed at the end of tumor resection and replaced the bone flap. The device was activated 9-14 days after surgery for a duration of 270 seconds every four weeks until progression or treatment completion, concomitantly with IV DEFINITY microbubbles (10 ml/kg, Lantheus, Billerica, US). The Phase 1 cohort consisted of an escalation of BBB disruption volume by activation of 3 (n = 3), 6 (n = 3), then 9 (n = 3) emitters of the device. Dose limiting toxicity (DLT) was assessed during the first two weeks after the 1st sonication. A subsequent expansion cohort consisted of patients treated with nine emitters in which the primary endpoint was assessment of BBB opening on MRI using gadolinium (< 1 hr after sonication). All patients received carboplatin either after (n = 21) or before (n = 12) device activation to disrupt the BBB. In addition, a sub-study was performed to investigate carboplatin concentration enhancement in the peritumoral region with sonication at time of device implantation. Study accrual is complete with 33 patients having been implanted and received at least one sonication. A total of 101 sonications were performed (range = 1-10 sonication sessions/patient). No DLTs were observed. Five serious adverse events (all resolved) were considered as possibly related to the study procedure. BBB disruption was confirmed by gadolinium enhancement after sonication. In three patients who underwent intraoperative sonication and carboplatin administration, a 7.58-fold increase in brain/plasma drug levels was demonstrated. Updated survival results will be presented.